Patterns of transgender microaggressions in friendship: the role of gender identity. Issue 3 (3rd July 2017) - Pulice-Farrow, Lex; Clements, Zakary A.; Galupo, M. Paz
ABSTRACT: Microaggressions are brief verbal, behavioural or environmental slights that communicate hostility or offence. Microaggressions that come from an individual's friends can be seen as more interpersonally aggressive and more upsetting than when coming from someone who the individual does not know. The present study examines transgender microaggressions that occur in friendships and specifically explores how microaggressions are experienced differently for transfeminine, transmasculine, gender nonconforming and agender individuals. Participants included 211 transgender adults who ranged in age from 18 to 65. Participants identified as transfeminine (28.4%), transmasculine (47.4%), gender nonconforming (18.0%) or agender (6.2%). Participants completed an online survey and provided qualitative information regarding their experiences of microaggressions from their friends. Responses were analysed via thematic analysis with a focus on explicating differences in experiences of microaggressions across gender identity. Three broad identity-salient themes emerged: (1) authenticity ; (2) visibility and (3) negotiation of identity in social context . Differences were seen between individuals endorsing binary (transfeminine and transmasculine) and non-binary (gender nonconforming and agender) identities, as well as between transmasculine and transfeminine identities. Discussion focuses on the way cisgenderism, sexism and binary assumptions about gender/sex converge to shape the experiences of transgender microaggressions in friendships.